Data sources used in bibliometric studies 1978-2022 - Hertil Lindelöw, Camilla (University of Borås, 2025)
This dataset contain data sources used in bibliometric studies. Every row corresponds to one data source so there will be multiple rows for articles containing multiple sources. The column norm_coarse corresponds to data source category and norm_fine to data source (only available for bibliographical metadata sources). See article for details.Related article: Lindelöw, C. H., Hammarfelt, B., & Mazoni, A. (2025). Data sources used in bibliometrics 1978–2022: From proprietary databases to the great wide open. Journal of the Association for Information Science and Technology, 1–14. https://doi.org/10.1002/asi.25018
Keywords: scientometrics; bibliometrics; information studies; biblioteks- och informationsvetenskap; Information Studies; Biblioteks- och informationsvetenskap